Diferentes estratégias de ensino e aprendizagem com equipe multiprofissional para cuidadores de pacientes em terapia nutricional enteral domiciliar - Afonso, Maria Gabriela (Universidade Federal de São Carlos, 2022)
Objective: To present different educational strategies used to get knowledge by caregivers in the care of patients using Enteral Nutritional Therapy. Method: Study has two stages, the first being a methodological study of construction and validation of the multiprofessional educational booklet for health education of caregivers and patients using Enteral Nutritional Therapy at home; and the second stage a quasi-experimental study, with a quantitative approach and descriptive character, composed of two phases. The first: Dialogued expository class (traditional education) all with all the participants and the second phase the participants are randomly divided into two groups being the reading of the educational booklet or the training of skills in a simulated clinical scenario. For Stage 1, judges were invited to validate the material through the "snowball" technique with inclusion according to the adapted criteria of Fehring, using the Delphi Technique to obtain maximum agreement from the judges. In the descriptive contributions, content analyzes were performed and the Content Validation Index was calculated. Participants in Stage 2 will be the caregivers of patients using Enteral Nutritional Therapy at home selected through a convenience sample, the selected caregivers must be the same to participate in all phases of the study. We will seek to summarize and organize the data obtained through statistical analyses.
Different teaching and learning strategies with a multidisciplinary team for caregivers of patients in Home Enteral Nutrition Therapy
Keywords: Educação em saúde; Nutrição enteral; Simulação; Equipe multiprofissional; Cuidadores; Education in health; Enteral nutrition; Multi-professional team; Caregivers; Simulation; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA